Pleomorphic adenoma‐like tumour of the breast. Issue 3 (28th July 2015) - Rakha, Emad A; Aleskandarany, Mohammed A; Samaka, Rehab M; Hodi, Zsolt; Lee, Andrew H S; Ellis, Ian O
Abstract : Aims: Pleomorphic adenoma (PA) of the breast is a rare tumour seen usually in postmenopausal women. Although PA of the salivary glands (SG) is recognized to be a benign tumour, the nature and biology of similar tumours seen in the breast remains to be defined. The aim of this study was to describe PA of the breast that was reported on core biopsy as an invasive matrix‐producing metaplastic breast carcinoma (MBC). Methods and results: A core biopsy from a clinically malignant retroareolar mass showed mildly atypical polygonal cells with surrounding myxoid stroma. Immunohistochemistry showed expression of basal and luminal cytokeratins, but oestrogen receptor, human epidermal growth factor receptor 2 (HER2) and myoepithelial markers were negative. The excision specimen showed similar features, but in addition the stroma showed cartilage and bone. Also it was clear that the lesion was circumscribed and merged with a sclerosed papillary lesion consistent with what has been described as mammary PA. Conclusion: This lesion shows an overlap of morphology and immunophenotype with SG‐PA and with MBC. The majority of mammary PAs have a benign behaviour, but local recurrence and development of carcinoma occur. We propose a new terminology of pleomorphic adenoma‐like tumour of the breast to reflect the uncertain nature of these tumours and help guide management decisions.